Analisis Fungsi Keluarga Pada Keluarga Nelayan di Desa Tanjung Baik Budi Kecamatan Matan Hilir Utara Kabupaten Ketapang - Mery Hendriana Putri (Indo Publishing, 2026)
This study aims to determine the function of the family through three functions, namely, educational function, economic function, love and affection function as a family function in fishermen families in Tanjung Baik Budi Village, Matan Hilir Utara District, Ketapang Regency. The observation method in this study, carried out through direct observation related to the observation of this study. 2. Interviews in this study make direct contact or oral communication to obtain data sources or information. 3. Documentation used in this study, includes collecting data that can support research during the observation process. And the data analysis uses 1. data reduction, 2. data presentation, and 3. conclusion drawing and verification. The results of this study indicate that the family function in fishing families in Tanjung Baik Budi Village, North Matan Hilir Utara District, Ketapang Regency is very influential on three family functions 1. The function of child education in fishermen's families, parents are responsible for providing education to their children, involved in children's learning, providing learning facilities and tools. 2. The economic function in fishing families fulfills the needs of food, clothing and shelter, provides advice, guidance on managing finances and teaches children not to live extravagantly. 3. The function of affection in fishing families, parents teach children a sense of empathy.